Selected thermal properties of cryo-ground coriander powder (var. RCR-41) - R Kumar, S N Saxena, P Barnwal, K K Singh, (Journal of Spices and Aromatic Crops, 2014)
Thermal properties of cryo-ground coriander powder (var. RCR-41) such as specific heat, bulk thermal conductivity and bulk thermal diffusivity were investigated. It was observed that the specific heat increased from 347.63 to 3700.31 J kg-1K-1 with increase in temperature from -150 °C to 100°C and moisture content from 3.5% to 17.7% (db) and it showed a second order polynomial relationship with moisture content and temperature. The thermal conductivity increased nonlinearly from 0.0884 to 0.1340 Wm-1K-1 with increase in moisture content from 3.5% to 17.7% (db) at 30°C. Thermal diffusivity varied non-linearly from 12.63 × 10-6 to 19.89 × 10-6 m2s-1 with increase in moisture content from 3.5% to 17.7% (db) at 30°C. Both thermal conductivity and thermal diffusivity showed quadratic relationships with moisture content. The specific heat was affected significantly with moisture content and temperature (P≤0.01) and both thermal conductivity and thermal diffusivity were affected significantly by moisture content.